Who Gets More of the Pie? Predictors of Perceived Gender Inequity at Work - Ngo, Hang-yue (Journal of business ethics, 2003)
Gender inequity is prevalent in the workplace. It violates the principle of equal treatment for all employees, and often leads to problems with retention, morale, and performance. Individuals, however, may have different perceptions of gender inequity. In this study, we examined the relationship between individual and organizational level variables and perceived gender inequity for a sample of church workers. Regression analysis was used to test several hypotheses informed by social psychological theories. The results showed that (1) individuals perceived gender inequity in the workplace; (2) organizational level variables had more effect on perceived gender inequity than individual level variables; and (3) compared to men, women perceived greater gender inequity favoring males. Discussion, limitations, and suggestions for future research are provided.